2014
DOI: 10.1002/asi.22986
|View full text |Cite
|
Sign up to set email alerts
|

Community detection based on social interactions in a social network

Abstract: Recent research has involved identifying communities in networks. Traditional methods of community detection usually assume that the network's structural information is fully known, which is not the case in many practical networks. Moreover, most previous community detection algorithms do not differentiate multiple relationships between objects or persons in the real world. In this article, we propose a new approach that utilizes social interaction data (e.g., users' posts on Facebook) to address the community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…We set limited capacity for each memory element is 10. The results of modularity measure for proposed algorithm as MLPA in comparison with other algorithm such as LPA [9], LPA-CNPE [16], LPA-CNP1 [16] and KLPA [15] are listed in table 4. figure 3, the results show a relative improvement in comparison with other community detection algorithms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We set limited capacity for each memory element is 10. The results of modularity measure for proposed algorithm as MLPA in comparison with other algorithm such as LPA [9], LPA-CNPE [16], LPA-CNP1 [16] and KLPA [15] are listed in table 4. figure 3, the results show a relative improvement in comparison with other community detection algorithms.…”
Section: Resultsmentioning
confidence: 99%
“…This heuristic was investigated over a maximization problem based on an adapted version of the clustering coefficient measure. In [9], researchers proposed a new method that utilizes social interaction data (e.g., users' posts on Facebook). Since many relationships are missing or not recorded, so they attempted to identify hidden communities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, [17] showed that, in social media, people form interlinked personal communities based on their follow and following connections as well as the norms, languages, and techniques used by them within the network. Somewhat differently, [9] argued that not all members are fully connected with each other and many relationships are missing in online social networks. They presented a new structure-based approach that leverages social communications (i.e., posts and replies) among users to identify different communities in which they engage.…”
Section: Related Work 21 Theoretical Motivations and Guidelinesmentioning
confidence: 97%
“…The structure‐based researches are usually based on an assumption that people's different types of friends tend to form separate clusters, or in other words, social groups. Some researches addressed the relationship identification problem as a community detection problem using unsupervised methods (Chen et al ). And other works (Tang et al ) developed a supervised method utilizing network structure information and evaluated their proposed Relationship Classification Algorithm (RCA) on Renren (www.renren.com) social network.…”
Section: Literature Reviewmentioning
confidence: 99%